A Integrating Letter Cards into Game-Based Learning (GBL) to Improve Elementary School Students' Understanding of the Javanese Script - Faricha Latifatul Hanifa; Anita Trisiana; Dite Hastini (Program Studi PGSD Universitas Madako Tolitoli, 2026)
Elementary school students' understanding of the Javanese script still shows limitations, especially in the ability to read, compose, and participate in learning. This study aims to describe the application and impact of the Game Based Learning (GBL) model through letter cards in grade V students of SD Negeri Beskalan Surakarta. The method used is classroom action research in two cycles which includes planning, implementation, observation, and reflection. The research subjects consist of teachers and students. Analysis is carried out through reduction, presentation, and drawing conclusions. Learning completeness increased from 45% with an average score of 60 in the initial condition to 72% with an average of 72 in the first cycle, then reached 92% with an average of 85 in the second cycle. Improvements also occurred in activeness, motivation, the ability to read and compose Javanese script, as well as student cooperation. These achievements indicate that the elements of games, interaction between students, the use of letter cards as concrete media, and active involvement are also other factors that improve student learning outcomes. These findings confirm the effectiveness of GBL in creating interactive, student-centered learning, and supporting the improvement of the quality of learning processes and outcomes.